2007
DOI: 10.1001/archpedi.161.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Emotional Health of Mothers of Youth With Functional Abdominal Pain

Abstract: Functional abdominal pain may be better conceptualized as a disorder of emotion than a narrowly defined disorder of gastrointestinal function. Low rates of mental health service use by mothers of youth with FAP suggest that family health and illness attitudes deserve study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
145
2
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(163 citation statements)
references
References 56 publications
8
145
2
8
Order By: Relevance
“…Parental anxiety levels and somatic symptom reporting has been examined in other pediatric conditions; mothers of children who suffer recurrent abdominal pain have significantly higher anxiety levels than comparison groups of mothers of healthy controls. [27][28][29] Additionally, parental depression and stress has been associated with reporting of pediatric neurologic symptoms, including headaches, vertigo, and syncope. 30 The objective of this study was to determine whether elevated parental anxiety at time of injury is a risk factor for PCS in children following acute concussion.…”
Section: Discussionmentioning
confidence: 99%
“…Parental anxiety levels and somatic symptom reporting has been examined in other pediatric conditions; mothers of children who suffer recurrent abdominal pain have significantly higher anxiety levels than comparison groups of mothers of healthy controls. [27][28][29] Additionally, parental depression and stress has been associated with reporting of pediatric neurologic symptoms, including headaches, vertigo, and syncope. 30 The objective of this study was to determine whether elevated parental anxiety at time of injury is a risk factor for PCS in children following acute concussion.…”
Section: Discussionmentioning
confidence: 99%
“…proposed that various mechanisms such as genetics, early life events, environmental, gastrointestinal and psychosocial factors act together in a complex interplay ultimately resulting in an alteration to the gut-brain axis 10,11,12,13,14,15,16 . Afferent signals from the gastrointestinal tract transmitted via the pain pathways are subsequently amplified and the patient's perception of painful stimuli is in turn enhanced 17 .…”
Section: Pathophysiologymentioning
confidence: 99%
“…Families of patients with FAP showed poorer communication among family members, higher role expectation, less affective responsiveness and involvement, a maladaptive problem-solving style and performed less well than families of control children. In two studies, Campo et al [35,38] found that mothers of children with FAP were less likely to be living with the child’s biological father, less likely to be married [38] and more likely to live alone with their child/children [35]. Logan and Scharff [39] explored whether parental and family characteristics are associated with children’s pain-related disability after accounting for the effects of pain intensity in families with children suffering from recurrent pain (headache, FAP).…”
Section: Two-stage Pathway Modelmentioning
confidence: 99%